2010
DOI: 10.1158/0008-5472.can-10-1033
|View full text |Cite
|
Sign up to set email alerts
|

Induction of DNA Damage-Inducible Gene GADD45β Contributes to Sorafenib-Induced Apoptosis in Hepatocellular Carcinoma Cells

Abstract: Markers that could accurately predict responses to the general kinase inhibitor sorafenib are needed to better leverage its clinical applications. In this study, we examined a hypothesized role in the drug response for the growth arrest DNA damage-inducible gene 45β (GADD45β), which is commonly underexpressed in hepatocellular carcinoma (HCC) where sorafenib may offer an important new therapeutic option. The anticancer activity of sorafenib-induced GADD45β expression was tested in a panel of HCC cell lines and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
52
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 36 publications
8
52
0
Order By: Relevance
“…The sorafenib-resistant HCC cell line, HuH-7 R , was established by long-term exposure of cells to sorafenib as previously reported (10).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sorafenib-resistant HCC cell line, HuH-7 R , was established by long-term exposure of cells to sorafenib as previously reported (10).…”
Section: Methodsmentioning
confidence: 99%
“…R Cells-Resistant HuH-7 R cell lines were established previously (10). As shown in supplemental Fig.…”
Section: Functional Analyses Of Huh-7 and Huh-7mentioning
confidence: 99%
“…Tumor volume and body weight were recorded every 7 days. At the end of drug treatment, tumor samples were collected for Western blotting, immunohistochemical analysis, and a terminal deoxynucleotidyl transferasemediated dUTP nick end labeling (TUNEL) assay (25).…”
Section: Tumor Xenograft Experimentsmentioning
confidence: 99%
“…9 It strongly inhibits different tumor cells including HCC cell proliferation and angiogenesis and induces apoptosis. Recent studies have suggested that sorafenib induced HCC cell apoptosis might be through induction of the growth arrest DNA damage-inducible gene 45b and an intrinsic mechanism where JNK-mediated PUMA up-regulation 47,48 Moreover, sorafenib was also reported to down-regulate the suppressive immune cell populations: Treg cells and myeloid-derived suppressor cells (MDSC) expression in a murine liver cancer model. 43 Another hot drug, mTOR pathways inhibitor, rapamycin as a single agent or in combination with other chemicals could inhibit tumor growth and angiogenesis in HCC in vitro and in vivo.…”
Section: Tumor Immunologymentioning
confidence: 99%